2011
DOI: 10.1002/maco.201106123
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition investigation and determination of some quantum chemical parameters of 1‐(4‐(dimethylamino)benzylidene)thiosemicarbazide on steel alloys in sulfuric acid medium

Abstract: The inhibition effect of 1‐(4‐(dimethylamino)benzylidene)thiosemicarbazide (DBT) on the corrosion behavior of 304 stainless steel and mild steel in 0.5 M sulfuric acid solution was investigated using weight loss and potentiostatic polarization methods. The experimental results suggest that DBT inhibits the corrosion of the steels in acid solution. The inhibition efficiencies increased as the concentration of the compound was increased. The calculated inhibition efficiencies from the two investigated methods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…The use of inhibitors is one of the most practical methods for protection against corrosion, especially in acidic media . The corrosion inhibition of steel by different types of organic compounds in acidic solution has been widely studied . Most of the acid inhibitors are organic compounds containing nitrogen , sulfur , and oxygen atoms.…”
Section: Introductioncontrasting
confidence: 99%
“…The use of inhibitors is one of the most practical methods for protection against corrosion, especially in acidic media . The corrosion inhibition of steel by different types of organic compounds in acidic solution has been widely studied . Most of the acid inhibitors are organic compounds containing nitrogen , sulfur , and oxygen atoms.…”
Section: Introductioncontrasting
confidence: 99%
“…Unavoidably, the corrosion problems are of great interest for the industries because they can cause enormous economic losses as well as safety hazards. One method of protecting it from corrosion is to use organic inhibitors, which are heterocyclic compounds containing P, S, O, or N and have π bonds . Owing to the toxicity of extensively used corrosion inhibitors and the ever tightening environmental regulations surrounding their use and disposal, there is great interest in replacing harmful inhibitors with effective non‐hazardous alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…The quantum chemistry computing method is often used to study the simple systems taking into account that (i) the effect depends only on the inhibitor molecule properties and (ii) everything else in its vicinity is uninvolved either with respect to competition for the surface or with respect to itself. Several researches confirmed that there is little effect of the media on these parameters [16][17][18][19][20]. Since, all metals are characterized by the presence of vacant d orbital which is ready to accept e's from donors (inhibitor molecules), the computing method is suitable for most metals.…”
Section: Discussionmentioning
confidence: 99%